Resiliensi Pedagang Pakaian Pasar Wage Kabupaten Tulungagung: Pilihan Rasional Pedagang Menghadapi Transformasi Pasar - Feriawan Kristanto; Waskito Waskito (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The development of traditional markets is increasingly threatened by market transformation, both physically and through online sales systems (e-commerce). This study aims to analyze the forms of resilience implemented by clothing vendors at Wage Market, Tulungagung, in maintaining their business continuity amidst declining market conditions. This study uses a qualitative approach with a case study research design. This research utilizes James S. Coleman's Rational Choice Theory. The methods used are observation, interviews, and documentation. The subjects in this study were six people consisting of four clothing vendors, the Head Coordinator of Wage Market, and the Heads of Market Technical Implementation Units throughout Tulungagung Regency. Subject selection was based on a purposive sampling technique. The results show that the forms of trader resilience consist of economic, innovation, social networks, and psychological aspects. Economically, traders maintain their businesses through managing capital owned by personal savings and cooperative loans. In terms of innovation, traders utilize simple technology and a variety of merchandise patterns. In terms of social networks, family support and solidarity among traders are the main strengths, while psychologically, optimism and religious beliefs help them survive. The implications of this research emphasize the importance of strengthening vendor strategies through digital marketing training and support for market revitalization policies from local governments to maintain the economic sustainability of vendors during times of market transformation.